2016
DOI: 10.1111/trf.13876
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusion‐transmitted acute hepatitis E in an immunocompetent subject in Europe: a case report

Abstract: Transfusion of RBCs with detectable HEV RNA is a risk factor for acute hepatitis E in immunocompetent patients in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 22 publications
1
27
0
1
Order By: Relevance
“…Before such a policy can be implemented, Spanish and EASL HEV guidelines have recommended that studies be carried out to evaluate the prevalence of HEV infection in blood donations across the different areas of influence of blood banks so that HEV screening strategies can be adapted to the relative prevalence of HEV infection in each . In this connection, the prevalence of HEV RNA in blood donations in studies performed in northeast Spain (Catalonia) was 1:3333 and 1:4720, and two cases of HEV transmission via this route have been documented . Our study carried out in south‐central Spain showed a similar prevalence of HEV infection among blood donors, which suggests a similar prevalence of HEV infection nationwide.…”
Section: Discussionmentioning
confidence: 88%
“…Before such a policy can be implemented, Spanish and EASL HEV guidelines have recommended that studies be carried out to evaluate the prevalence of HEV infection in blood donations across the different areas of influence of blood banks so that HEV screening strategies can be adapted to the relative prevalence of HEV infection in each . In this connection, the prevalence of HEV RNA in blood donations in studies performed in northeast Spain (Catalonia) was 1:3333 and 1:4720, and two cases of HEV transmission via this route have been documented . Our study carried out in south‐central Spain showed a similar prevalence of HEV infection among blood donors, which suggests a similar prevalence of HEV infection nationwide.…”
Section: Discussionmentioning
confidence: 88%
“…The implicated donor had occupational exposure in a sausage factory. Platelets from the same infected donation were transfused to a Hodgkin lymphoma patient who died shortly after transfusion [43]. Selective HEV screening of blood donations is under consideration taking into account logistical challenges.…”
Section: Hepatitis E Virus and Blood Donations In Selected European Cmentioning
confidence: 99%
“…Blood donor research in south central Spain (October 2017 to March 2018) identified 1 in 1,524 HEV-RNA-positive donations (MP-8 using RT-PCR; 0.06%) with VL ranging from ∼10,000 to 2,000,000 IU/mL [42]. In Spain, 1 confirmed case of TT-HEV infection (GT 3f) has been reported [43]. …”
Section: Overview Of Eu Blood Donor Screening Methods and Strategiesmentioning
confidence: 99%